First record of the bat Artibeus jamaicensis in the diet of the Common Black Hawk (Buteogallus anthracinus) in the Neotropics - José Alberto Gómez-Ortega; Laura Teresa Hernández Salazar; Edgar Ahmed Bello Sánchez; Jéssica Alejandra Jiménez Martínez; Jorge Éufrates Morales Mávil (Huitzil, 2025)
The Common Black Hawk (Buteogallus anthracinus) is a raptor that feeds mainly on crustaceans and fish, but is an opportunistic consumer that can also feed on other prey. We visited the El Cantil Blanco cave in Veracruz, Mexico, located in deciduous lowland forest and secondary vegetation, to study bats. On 18 December 2023, we observed two Common Black Hawks at the entrance to the cave. One hawk was holding a dead bat, which it dropped as we approached. On inspecting the site below the hawk’s perch, we found remains of Artibeus jamaicensis bats. Our results provide the first record of A. jamaicensis bats in the diet of this raptor in the Neotropics, which is notable considering the few records of mammals in the diet of this raptor.